EXAMINING THE MEANING IN THE LYRICS OF THE BUAI ANAK SONG - Suhadri , Fadlika; Minawati , Rosta; Mulyadi (Journal of Learning on History and Social Sciences, 2024)
Objective: This study examines the emotional and educational themes depicted in the song "Buai Anak," focusing on the role of the mother in the upbringing of her child. The research aims to analyze the cultural and moral values conveyed through the lyrics and their connection to family life in Indonesian society. Method: A semiotic approach was used to interpret the symbols and signs present in the song's lyrics. The analysis focused on the expressions that represent a mother's emotional closeness, hopes, and prayers for her child. Additionally, the study explored the cultural and social context of Indonesian family dynamics, incorporating relevant historical and societal perspectives. Results: The song "Buai Anak" reflects the universal themes of maternal love, sacrifice, and perseverance. The lyrics portray both the sweet and bitter moments in the mother-child relationship, highlighting the importance of values such as patience, love, and education. The song also communicates a moral message about the significance of role models and the need for peace within the family. Novelty: This study emphasizes the profound cultural and educational messages embedded in the song, offering insights into how traditional Indonesian values related to family, education, and generational relationships are transmitted through music. The analysis also sheds light on the song's broader impact, encouraging listeners to reflect on their own family bonds and the deeper meanings of life.